2016
DOI: 10.1061/(asce)cp.1943-5487.0000563
|View full text |Cite
|
Sign up to set email alerts
|

Condition Assessment of Timber Utility Poles Based on a Hierarchical Data Fusion Model

Abstract: This paper proposes a novel hierarchical data fusion technique for the non-destructive testing (NDT) and condition assessment of timber utility poles. The new method analyses stress wave data from multi-sensor multi-excitation guided wave testing using a hierarchical data fusion model consisting of feature extraction, data compression, pattern recognition and decision fusion algorithms. The proposed technique is validated on guided waved at a of in-situ timber poles. The actual health states of these poles are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The numerical and experimental tests dealing with the wave propagation phenomenon in the isotropic and anisotropic materials confirm the serviceable of this method in the damage detection systems [12,13]. Yu et al demonstrated the effectiveness of the wave propagation analysis in the wood utility poles what proves the versatility and possibility of matching the measurement techniques to the specific subject of analysis [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 88%
“…The numerical and experimental tests dealing with the wave propagation phenomenon in the isotropic and anisotropic materials confirm the serviceable of this method in the damage detection systems [12,13]. Yu et al demonstrated the effectiveness of the wave propagation analysis in the wood utility poles what proves the versatility and possibility of matching the measurement techniques to the specific subject of analysis [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 88%
“…The concept is described briefly. SVM is a supervised machine-learning algorithm and is widely used as a promising tool [25][26][27].…”
Section: Fault Diagnosis Based On Svmmentioning
confidence: 99%
“…Principal components (PC1 and PC2 combined) can successfully detail 80% of the variance of the data-set, which can decrease to 70% for ecological observations due to inherent variability [ 16 ]. PCA is used in a wide spectrum of industries for different purposes, including process yield prediction of protein-A chromatography in bioengineering, identifying critical pollutants and their sources in environmental monitoring system, minimizing information redundancy in civil engineering, predicting the effects of drugs on behavioral brain research, and so on [ 15 , 16 , 17 , 18 , 19 ]. This novel multivariate statistical tool offers the reliability to formulate an ideal point that will represent an industry grade natural fibre where all the fibre characteristics are within prescribed standard limits set by material scientists or engineers.…”
Section: Introductionmentioning
confidence: 99%